The Influence of Leadership Style, Compensation, and Worker Discipline On Performance KCP BRI Gading Boulevard Raya - Anggara, Ricko; Saluy, Ahmad Badawi (Dinasti International Journal of Digital Business Management, 2023)
Comparatively speaking to other economic sectors, the banking sector in Indonesia has developed more rapidly than others. Because there is fierce competition amongst banking sector players on both a local and global scale, the industry as a whole must adapt to changes faster. including PT BRI, one of the banks that propels the economy; BRI is a bank that advocates for the expansion of MSME businesses in Indonesia and focuses on the MSME sector. The goal of this research is to ascertain how worker discipline, pay, and leadership style affect output. As a scientist, the author employs a quantitative research strategy since the data is observable, measurable, rational, and methodical. The population of this study consisted of 105 employees of the BRI Sub-Branch Office (KCP) Gading Boulevard Raya, and 83 respondents were selected from the non-probability sample method using purposive sampling approach. The Slovin formula is utilised to determine the sample count. In this work, a Structural Equation Model (SEM) based on Partial Least Square (PLS) 3.0 assists with the data processing technique. The study's findings imply that a leader's kineirja at KCP BRI Gading Bouileivard Raya Kanca Jakarta Artha Gading may be positively and significantly impacted